2008
DOI: 10.1007/s00404-008-0861-7
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib use during pregnancy and breast feeding: a case report and review of the literature

Abstract: In light of reported cases and our experience, treatment of CML during the second and third trimesters of gestation and breast feeding seems to be safe, but the data are still limited and the effects of chronic exposure of infants to imatinib are not known. We think that each case should be examined and considered independently, and decisions should be individualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 31 publications
0
37
0
3
Order By: Relevance
“…Imatinib was found to be present at high concentration in the maternal blood and in the placenta; however, minimal or no drug was detected in the cord blood, suggesting that imatinib and its active metabolite cross the mature placenta poorly. A subsequent report by Ali et al [43] on imatinib exposure in pregnancy from the 21st to 39th week of gestation revealed that imatinib was present at 338 ng/mL in the cord blood and 478 ng/mL in the peripheral blood of the newborn compared to 1562 ng/mL in the maternal blood. There were no maternal-foetal complications observed in these cases.…”
Section: Treating CML In Pregnancymentioning
confidence: 93%
“…Imatinib was found to be present at high concentration in the maternal blood and in the placenta; however, minimal or no drug was detected in the cord blood, suggesting that imatinib and its active metabolite cross the mature placenta poorly. A subsequent report by Ali et al [43] on imatinib exposure in pregnancy from the 21st to 39th week of gestation revealed that imatinib was present at 338 ng/mL in the cord blood and 478 ng/mL in the peripheral blood of the newborn compared to 1562 ng/mL in the maternal blood. There were no maternal-foetal complications observed in these cases.…”
Section: Treating CML In Pregnancymentioning
confidence: 93%
“…week of gestation, and was present at 338ng/mL in the cord blood and 478 ng/mL in the peripheral blood infant (1/3 range) vs 1562 in maternal blood [48]. Summary of product characteristics recommend that all TKIs should not be used during pregnancy, in case of need, imatinib could be considered after the placenta is completely formed (12-14 weeks), and nilotinib even earlier, while dasatinib should never be used during all pregnancy.…”
Section: Diagnosed During Pregnancymentioning
confidence: 98%
“…Some reports in literature indicate that patients who receive imatinib at the time of conception may have normal pregnancies. [67][68][69][70][71][72][73][74] Dasatinib and nilotinib are known to cause embryonic or fetal toxicities in animals. Isolated reports can be found in the literature regarding the outcome of pregnancy in patients receiving dasatinib [75][76][77] or nilotinib.…”
Section: Tki Therapy and Conceptionmentioning
confidence: 99%